The Genetic Characterization of DGAT1 Gene in Donkey Populations Reared in Thrace Region of Turkey - Fulya Özdil (Journal of Agricultural Sciences)
AcylCoA: diacylglycerol acyltransferase (DGAT1) gene has a considerable effect on milk content and yield in cattle with a substitution of lysine by alanine in the exon 8 of the gene. Moreover there are many other researches comprising the DGAT1 gene on different farm animals, such as buffalo, sheep and goat but there is no information about the DGAT1 gene in donkeys. In this study, the polymorphism of DGAT1 gene in donkey populations reared in Thrace region of Turkey has been investigated by restriction fragment length polymorphism (RFLP) via EaeI (CfrI) restriction enzyme. EaeI restriction site was found in cattle breeds which resulted after K232A substitution, Lysine (AAG) to Alanine (GCG) variant but this restriction site was not found in donkey populations. A novel single-nucleotide polymorphism (GA substitution) in the DGAT1 gene at position 10,435 lacks this restriction site which results only Alanine variant (GCA) instead of Lysine variant. This novel single-nucleotide polymorphism in the DGAT1 gene was found in the studied donkey breeds.